Does Human Resource Management Practices differ at different Job Categorical in Sugarcane Farming Organization? - Dini Damayanthy; Suhatmini Hardyastuti; Irham Irham; Muhammad Yamin (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2023)
Human resource management practices are implemented for achieving thecompany's business sustainability. Otherwise, many companies have not realized the importance of implementing human resource management practices themselves. This study aims to analyzing the implementation of human resource management practices based on technical and non-technical employees in two different work units, namely the head office and the factory at a sugarcane plantation company in East Java Province. Approximately 150 employees selected through the proportional random sampling method from two work units and different job categories were involved as the inside sample. This research uses inferential statistical analysis method. The results of the study show that technical and non-technical employees who work in two different work units have different responses to the implementation of human resource management practices that have been implemented. Differences that occur due to differences in competency requirements and work units are also different. Furthermore, the results of the study show that compensation and career development are two variables that are considered to still need more attention and improvement from the company. Overall, the research results can also be used as material for evaluation and policy recommendations for the implementation of human resource management in companies.